Room-temperature asymmetric transfer hydrogenation of biomass-derived levulinic acid to optically pure gamma-valerolactone using a ruthenium catalyst - Shende, Vaishali S.; Raut, Amol B.; Raghav, Prathamesh; Kelkar, Ashutosh A.; Bhanage, Bhalchandra M. (ACS Omega, 2019)
This study presents a first report on ruthenium-catalyzed asymmetric transfer hydrogenation (ATH) of levulinic acid (LA) to chiral gamma-valerolactone (GVL). ATH of LA has been explored with Noyori's chiral catalyst (Ru-TsDPEN) in methanol solvent. Efficacy of ATH reaction of LA was investigated under different reactions conditions such as temperature, catalyst, and hydrogen donor concentration. The effect of various organic tertiary bases along with formic acid (FA) as a hydrogen donor was studied, and N-methylpiperidine with FA (1:1 molar ratio) was revealed as an efficient hydrogen donor for ATH of LA to GVL furnishing chiral GVL with complete conversion and 93% enantiomeric excess (ee). This operationally simple and mild ATH protocol was tested for practical applicability of ATH of LA obtained from biomass waste (rice husk and wheat straw) and furnished chiral GVL with 82% ee.